What are the chances of war?. Issue 2 (April 2016) - Cirillo, Pasquale; Taleb, Nassim Nicholas
Abstract : Pasquale Cirillo and Nassim Nicholas Taleb respond to December's "Ask a Statistician" column, explaining more about their work to understand the risk of violent conflicts Abstract : Pasquale Cirillo andNassim Nicholas Taleb respond to December's "Ask a Statistician" column, explaining more about their work to understand the risk of violent conflicts